A Comparison of Real-Time Extraction between Chebyshev and Butterworth Method for SSVEP Brain Signals - Kusumandari, Dwi Esti; Hidayat, Taufik; Turnip, Arjon (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
In this paper, a comparison of real-time extraction using the IIR Chebyshev of 4 order and the IIR Butterworth of 6 order methods is proposed. In the Experiment, the steady-state visual evoked potential with stimuli frequencies of 7,5 10, 15, and 20 Hz is used to control the wheelchair directions (i.e., stop, forward, right, and left). The data were collected from a session in which fourteen subjects with age about 24±2 years were tested. The total average classification accuracy of 82% and 62.2% for Chebychev and Butterworth extraction method are achieved. The higher average classification accuracy of 100% and 92.8% for both methods, respectively, are obtained for forward direction (8.75-12.5Hz).